PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MENGGUNTING DAN MENEMPEL PADA ANAK USIA 4-5 TAHUN DI PAUD AISYIYAH 3 PONTIANAK - Sarina, Sarina; Ali, Muhammad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this study is to know: 1) Learning planning with cutting and sticking activities to improve fine motor skills in children aged 4-5 years in PAUD Aisyiyah 3 with, 2) Implementation of learning through cutting and sticking activities to improve fine motor skills in children aged 4-5 years in early childhood Aisyiyah 3 Pontianak and 3) Improvement of fine motor skills of children after following the activity of cutting and sticking to children aged 4-5 years in early childhood Aisyiyah 3 Pontianak. Researchers use descriptive method. The form of this research is classroom action research. Data analysis used in this research is observation, and interview. The steps used in this study are as follows: 1). Planning, 2). Implementation, 3). Observation or Observation and 4). Reflection. Data analysis techniques used are observation / observation and interview / conversation and gathering tool is the format of observation and interview guide. The result of the research shows that 1) Learning planning using cutting and sticking technique to improve fine motor in accordance with the steps that have been determined in improving the fine motor of the child with the category is not arranged in cycle 1 and in cycle II with the categories well arranged. 2) Implementation of learning using cutting and sticking techniques to improve fine motor has been implemented by the teacher well as according to the planning prepared by the teacher, both in cycle I and cycle II and 3) Improvement of fine motor development of children after following learning by cutting techniques and attached, progressed very well in cycle I mean motor fine of child equal to 59,29 and increase in cycle II become 89,41. This means the fine motor of the child has improved very well.Â Keywords: Smooth Motorcycle, Cutting, Sticking.Â